Development of a tool to study aircraft trajectory optimisation in the presence of icing conditions. (June 2015) - Shinkafi, Ahmed; Lawson, Craig
With the increasing demand of air travel, the impact on the environment due to aviation has shown a significant increase in recent times. As a result, there is a growing demand for new technologies and flight procedures that will enable aircraft operators to burn less fuel and reduce the adverse effect of aviation on the environment. Conventional approaches to trajectory optimisation do not take the effect of aircraft systems into account. Neglecting these effects may be inadequate, especially when one considers real aircraft operations in real weather scenarios. This research has developed a tool capable of simulating aircraft ice protection performance for trajectory optimisation, which enables the development of a decision making process dependent on weather within the flight management system, thus transforming the conventional ice protection system to a more intelligent system. Presently, thermal ice protection methods are the leading ice protection technology on most of the medium and large transport aircraft. An enhanced aircraft anti-icing model was developed based on Messinger mass and energy balance method for thermal anti-icing. The tool developed in this work can calculate the total water catch and evaluate power requirement due to icing under a wide range of meteorological conditions. The model was successfully integrated with a trajectory optimisation framework for independent assessment of fuel penalty due to icing and investigation of pollutant emissions reduction through aircraft trajectory optimisation. A case of typical departure from London Airport Heathrow was optimised for fuel burn and time. The preliminary results show that when operating in known icing condition, including icing parameters in the optimisation loop could give as much as 2.1% fuel savings.